Liuwei Dihuang Lowers Body Weight and Improves Insulin and Leptin Sensitivity in Obese Rats. (4th September 2011) - Perry, Benjamin; Zhang, Junzeng; Sun, Changhao; Saleh, Tarek; Wang, Yanwen
Abstract : The present study was aimed at investigating the efficacy and mechanism(s) of action of a Chinese herbal formulation, Liuwei Dihuang (LWDH), as a prospective natural weight-lowering product. Following a 2-week acclimation period, 48 obesity-prone (OP-CD) rats were divided into 4 groups (n = 12 each). One group served as a positive control for obesity (OP), while the other 3 were challenged twice daily by oral gavage with total daily dosages of 500, 1500, or 3500 mg/kg BW LWDH, respectively, for 10 weeks. One group (n = 12 ) of obesity-resistant (OR-CD) rats served as the normal control group. All rats were fed the same AIN-93G diet modified to contain 60% energy from fat. The highest LWDH dose significantly reduced body weight during the last 4 weeks of treatment. Food intake was reduced beginning in week 2. The high LWDH dose lowered serum triglyceride (TG) and nonesterified fatty acid (NEFA) levels and body fat. Both the high and medium doses also lowered serum leptin and insulin levels. Liver function testing revealed no adverse side effects under the current experimental conditions. The results of the present study suggest that LWDH has potential as a preventive or therapeutic natural product against overweight and obesity.